An Exploratory Cross-Cultural Study of Virtual Library Tourism: User Experiences at the National Library of the Republic of Indonesia - Rejeki, Diah Sri; Wahyuni, Haria Saputry; Ariff, Nor Zaina Zaharah Mohd (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study investigates the cross-cultural perceptions of Indonesian and Malaysian students regarding the virtual literacy tourism services offered by the National Library of the Republic of Indonesia. As part of ongoing digital transformation efforts in the literacy sector, these virtual tour services provide an alternative means of accessing information and promoting cultural heritage. The purpose of this research is to analyze perceptual differences between the two student groups using user experience theory, which encompasses cognitive, affective, and cultural dimensions. A quantitative comparative design was employed, involving a purposive sample of 100 participants, 50 students from Indonesia and 50 students from Malaysia. Data were collected through an online questionnaire using a 5-point Likert scale and analyzed through descriptive statistics and independent sample t-tests. The findings reveal that, overall, there are no significant differences between the two groups across most indicators. However, a notable distinction appears in the affective dimension, specifically the sense of presence, which is higher among Malaysian respondents. These results indicate that user experience is shaped by cultural context and highlight the potential of virtual library tours to foster cross-cultural engagement and understanding.